Integrated Policy Strategies for Addressing Out-of-School Children (OSC) in Metro City - Yuli Yanto (JURNAL ILMIAH GEMA PERENCANA, 2026)
Education is a fundamental right; however, Metro City faces an anomaly where 526 children remain out of school (ATS) despite achieving a "Very High" Human Development Index (HDI). This study aims to identify the root causes of Out-of-School Children (OSC) and formulate integrated management strategies. The methodology employs a qualitative approach, utilizing the Urgency, Seriousness, and Growth (USG) method for priority analysis and a Fishbone Diagram for root cause identification.The findings indicate that family economic status is the primary determinant (highest USG score of 14), where poverty remains the driving force behind children leaving school in Metro City. Other contributing factors include early marriage, limited accessibility for people with disabilities, and an unconducive school climate resulting from bullying. The discussion emphasizes the necessity of implementing policies based on human capital theory and social ecology to foster an inclusive educational environment. The study concludes that addressing OSC in Metro City requires simultaneous rather than fragmented policies. The proposed recommendation is the enactment of a Metro Mayoral Regulation on the Regional Action Plan for Handling Out-of-School Children (RADPATS). The regulatory substance should focus on: Strengthening social protection through the validation of the National Socio-Economic Single Data (DTSEN) to ensure targeted distribution of aid, such as the Kartu Metro Bahagia; Enhancing educator competence to establish Child-Friendly Schools (SRA); and Integrating OSC management programs into regional planning documents (RPJMD/RKPD) by involving a pentahelix of stakeholders.